1993
DOI: 10.1016/0014-5793(93)80035-s
|View full text |Cite
|
Sign up to set email alerts
|

Bovine inositol monophosphatase: proteolysis and structural studies

Abstract: Bovine brain inositol monophosphatase is inactivated when trypsin catalyses the cleavage of a single peptrde bond between Lys-36 and Ser-37. This proteolysis is closely followed by cleavage at two other sites in the protein between Lys-78 and Ser-79 and between Lys-156 and Ser-157 suggesting that all of these sites are exposed in the native conformation of the protein. All of these residues are predicted to lie at the ends of a helices. The most susceptible bond (Lys-36Ser-37) is predicted to lie in a highly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Since the K,,, for the metal ion is dependent upon the substrate used, these studies are the first to monitor the fundamental metal-protein interactions. Limited proteolysis by trypsin has been demonstrated to cleave the peptide bond between Lys36 and Ser37, effectively, removing a peptide element that is thought to move during catalysis [24]. Previous studies have shown that this treatment eliminates the activity of the enLyme and fluorescence studies have indirectly supported the proposal that this is probably achieved by also eliminating the binding of Mg" to site 1.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Since the K,,, for the metal ion is dependent upon the substrate used, these studies are the first to monitor the fundamental metal-protein interactions. Limited proteolysis by trypsin has been demonstrated to cleave the peptide bond between Lys36 and Ser37, effectively, removing a peptide element that is thought to move during catalysis [24]. Previous studies have shown that this treatment eliminates the activity of the enLyme and fluorescence studies have indirectly supported the proposal that this is probably achieved by also eliminating the binding of Mg" to site 1.…”
Section: Discussionmentioning
confidence: 76%
“…To 1 ml of inosito1 monophosphatase (1 mg/ml) was added 20 pl of 0.1 mg/ml trypsin in 10 mM Tris/HCl, pH 8.0, at 21 "C. Samples were withdrawn at various times and either assayed for activity [22] or run on a 12% SDYPAGE gel for verification that a single cleavage of the protein had occurred [24].…”
Section: Methodsmentioning
confidence: 99%
“…A sample of the pyrene-labelled enzyme was subjected to partial proteolysis by trypsin, previously shown to cleave specifically between Lys-36 and Ser-37 [25]. Such treatment leads to the loss of a 36-amino-acid peptide from the N-terminal end of the protein, resulting in complete loss of enzyme activity [25]. Stopped-flow fluorescence studies using these enzyme species showed that neither the fast nor the slow change in fluorescence intensity occurred from the pyrene moiety on mixing with Mg# + ions.…”
Section: Effect Of Limited Proteolysis By Trypsin On Both Phases Of Tmentioning
confidence: 99%
“…The epitope of the antibody is centred around Cys-8 [23], and binding gives rise to inhibition of the enzyme [23]. Furthermore, limited proteolysis studies using endoproteinase Lys-C [24] and trypsin [25] have demonstrated that the bond between Lys-36 and Ser-37 in inositol monophosphatase is highly susceptible to proteolysis. Hydrolysis of this bond leads to a concurrent loss of enzyme activity, suggesting that this region of the protein is important in the functioning of the enzyme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation